Powdered beverage mix with acerola pulp, whey and maltodextrin - Lima, Natalia; Afonso, Marcos; Costa, José Maria; Carvalho, Juliane (Revista Ciência Agronômica, 2019)
Mixing acerola pulp with whey, a by-product of the dairy industry, led to this study, whose aim was the development of a powdered beverage mix of acerola pulp, whey and maltodextrin (DE20). To determine the proportions of the mixture, a simplex-centroid mixture design was used. Different proportions of the mixture were dehydrated in a spray dryer at 175 °C. The results were evaluated in relation to hygroscopicity, moisture and ascorbic acid. Higher proportions of whey and pulp increased hygroscopicity and moisture, while maltodextrin reduced these parameters. An increase in pulp content raised the levels of ascorbic acid. The proportions (m m-1) of 50% acerola pulp, 25% whey and 25% maltodextrin resulted in significantly lower hygroscopicity (8.25 g 100 g-1) and moisture (1.66%), and appreciable levels of ascorbic acid (1492.49 g 100 g-1). The results indicated that the powder obtained shows good stability after 75 days of storage, with 9.20%, 1.79% and 1146.13 g 100 g-1 of hygroscopicity, moisture and ascorbic acid respectively.